2021
DOI: 10.3390/ma14020421
|View full text |Cite
|
Sign up to set email alerts
|

Current and New Approaches to Predict the Deflections of One-Way Flexural Members with a Focus on Composite Steel Deck Slabs Voided by Circular Tubes

Abstract: A new type of composite voided slab, the TUBEDECK (TD), which utilizes the structural function of profiled steel decks, has recently been proposed. Previous studies have confirmed that the flexural strength of TD slabs can be calculated based on the full composite contribution of the steel deck, but for long-span flexural members, the deflection serviceability requirement is often dominant. Herein, we derived a novel deflection prediction approach using the results of flexural tests on slab specimens, focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, although it is given for the solid members, ACI318-19 [66] and Eurocode 2 [60] was stated to be utilized to calculate the moment capacity of the voided slabs [23,32]. Contrarily, Lee et al [67] indicated that cracking moment predictions made in ACI318-19 [66] were nonconservative for voided slabs. None of the studies proposed an equation considering the effects of voids on moment capacity.…”
Section: Recommended Moment Capacitymentioning
confidence: 99%
“…Therefore, although it is given for the solid members, ACI318-19 [66] and Eurocode 2 [60] was stated to be utilized to calculate the moment capacity of the voided slabs [23,32]. Contrarily, Lee et al [67] indicated that cracking moment predictions made in ACI318-19 [66] were nonconservative for voided slabs. None of the studies proposed an equation considering the effects of voids on moment capacity.…”
Section: Recommended Moment Capacitymentioning
confidence: 99%